1985
DOI: 10.1021/bi00323a031
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from carbon-13 NMR for polarization of the carbonyl of oxaloacetate in the active site of citrate synthase

Abstract: The carbon-13 NMR spectrum of oxaloacetate bound in the active site of citrate synthase has been obtained at 90.56 MHz. In the binary complex with enzyme, the positions of the resonances of oxaloacetate are shifted relative to those of the free ligand as follows: C-1 (carboxylate), -2.5 ppm; C-2 (carbonyl), +4.3 ppm; C-3 (methylene), -0.6 ppm; C-4 (carboxylate), +1.3 ppm. The change observed in the carbonyl chemical shift is successively increased in ternary complexes with the product [coenzyme A (CoA)], a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 25 publications
3
62
0
Order By: Relevance
“…Polarization of the thioester carbonyl group has been observed by vibrational and NMR spectroscopies for a number of CoA-dependent enzymes (34,(57)(58)(59)(60)(61) including the acyl-CoA dehydrogenases (54,55). In particular, the polarization seen in this work shows striking parallels with that observed for the binding of cinnamoyl-CoA analogues to enoyl-CoA hydratase (34,59) and benzoyl-CoA derivatives to 4-chlorobenzoyl-CoA dehalogenase (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Polarization of the thioester carbonyl group has been observed by vibrational and NMR spectroscopies for a number of CoA-dependent enzymes (34,(57)(58)(59)(60)(61) including the acyl-CoA dehydrogenases (54,55). In particular, the polarization seen in this work shows striking parallels with that observed for the binding of cinnamoyl-CoA analogues to enoyl-CoA hydratase (34,59) and benzoyl-CoA derivatives to 4-chlorobenzoyl-CoA dehalogenase (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…This would favor a large positive partial charge on C-3 of oxaloacetate, making it susceptible to nucleophilic attack. Kurz and Drysdale {24,25) have reported NMR and Fourier transform IR studies which indicate that the carbonyl carbon-oxygen bond is strongly polarized.…”
Section: A Enzyme-bound Citrate and Oxaloacetatementioning
confidence: 99%
“…Significant binding isotope effects have also been measured in the reaction catalysed by human brain hexokinase (Lewis and Schramm, 2003), lactate dehydrogenase (LaReau et al, 1989;Gawlita et al, 1995a, b), phosphoenolpyruvate carboxylase (Gawlita et al, 1995a, b), and pyruvate kinase (Gawlita et al, 1995a, b). Furthermore, a number of spectroscopic studies have demonstrated significant polarization of substrate carbonyls upon binding enzyme and prior to catalysis that would be expected to yield corresponding isotope effects on the binding steps (Belasco and Knowles, 1980;Kurz et al, 1985;Deng et al, 1989Deng et al, , 1992Tonge and Carey, 1992). Effects such as these also can be viewed as potential contributors to any measured kinetic isotope effect intended to evaluate the transition state during the step of actual covalent rearrangement.…”
Section: Introductionmentioning
confidence: 99%